Agentes inteligentes para la gestión de recursos digitales de aprendizaje. - Condoy Carrión, Alex Rubén (2019)
Although technological advances have implied changes in the educational paradigm, such as mass access to information, virtual education, virtual learning environments, among others; there is still a traditional model where the teacher is the only one in charge of preparing the topics, resources and teaching methods; But not all the students will learn in the same way, and that is why it is appropriate to propose an alternative method that involves the student more in this process, taking into account that they have emotional intelligences, multiple intelligences and different learning styles. The goal of this work is to implement an architecture of multi-agent system (prototype), for the management of digital learning resources (learning objects); Aiming to this, the research question is: How does the implementation of smart agents influence the management of digital learning resources, according to the intelligence profile of each student (learning styles and multiple intelligences)? The present final project (TT) was executed in three phases. The first one, through a systematic literature review (SLR) the tools and methodologies for multi-agent systems (SMA) were identified: INGENIAS for the development of SMA, Methontology for the development of ontology (metadata management), and JADE for the implementation of the SMA architecture. As a second phase, we developed an SMA prototype, which recommends learning objects (OAs) based on each user's profile, these OAs are consulted from the ROA-CEDIA, ViSH, EducaInternet repositories, and managed by the architecture of the SMA, consisting of: an interface agent, searching agent, repository managing agent, coordinating agent and the student profile agent. In the third phase, the prototype was implemented in a Web server for architecture evaluation; first, technical tests and ontology tests were performed through JMeter and the triangular method respectively; later, an academic experimentation, in which participated the students of the “Carrera de Ingeniería en Sistemas” of the “Universidad Nacional de Loja”, verifying that the ease of use and acceptance are quite appropriate. In conclusion, the management of digital learning resources (OAS) through an SMA, can positively influence by linking it to a smart classroom in the tasks of resource management based on user preferences, for instance.